Chrześcijanie w otoczeniu szacha. Problem inkulturacji na podstawie ustawodawstwa synodalnego Kościoła orientalnego przełomu V i VI wieku - Żelazny, Jan W. (Vox Patrum, 2015)
In the late 5th century, disciplinary practices of the Assyrian Church of the East saw an unprecedented change in the scope of marriages of priests and those serving the God. Synods in Saliq in 486 and 497 agreed not only to consecrate married men but also to allow already consecrated priests and bishops to get married. The synods lifted restrictions on successive bigamy (marriages of widows and widowers) as well. Abstinence as such was limited and priests were allowed to maintain contacts with their wives and have children. This was the key issue for bishops participating in the debate although history remembered the assemblies as proclaiming the Nestorian confession of faith. The matter of adaptation to standards of the Persian society was very pressing, with both resolutions and the course of the debate showing clear intervention of Persian sovereigns. Adopted arrangements remained binding to a greater or lesser extent for over half a century and although they did not introduce any permanent change in the Church discipline, they represent an interesting example of an attempt to adjust the canon law to the social context of the life of Christians in the Persian Empire.